Retention of metal brackets bonded on acrylic teeth with different surface preparation and its impact on oral health related quality of life of orthodontic patient: a preliminary study / Mohd Helmi Mahamad Nazir - Mahamad Nazir, Mohd Helmi (2022)
This research aims to evaluate and compare the retention of metal brackets bonded onto acrylic teeth with different surface preparation methods, to measure the impact of the acrylic teeth towards patient’s function, appearance, and social life throughout the study, and to assess the impact of the acrylic teeth towards patient’s Oral Health-Related Quality of Life (OHRQoL) Orthodontic patients aged between 18 and 35 years who had at least one missing tooth, and required space idealisation for any prosthesis, were recruited. Patients were randomised into four different surface preparation method. Group 1: Transbond XT adhesive only; Group 2: Transbond adhesive XT with surface sandblasting; Group 3: Transbond XT adhesive with surface abrasion; and Group 4: Triad Gel adhesive only. Once the space was adequate, the prepared tooth was ligated to the arch-wire. The attachment between acrylic teeth and metal bracket was monitored and recorded in attachment days for six months.